Representation of Mathematical Concepts in Alan Becker’s “Animation vs Math” Video: Semiotic Analysis Educational - Hasan Fauzi; Nanang Nabhar Fakhri Auliya; Rizqona Maharani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
Difficulties in understanding mathematics are often caused by its abstract nature, exacerbated by learning methods that lack variety. The use of animated media offers a potential solution to facilitate abstract concepts through visualization. The purpose of this study is to analyze how Alan Becker's video “Animation vs. Math” represents mathematical concepts and to examine its relevance to the learning outcomes of mathematics in the Merdeka Curriculum. This study uses a descriptive qualitative approach with Charles Sanders Peirce's semiotic analysis method, which refers to sign analysis (index, icon, and symbol). Data were collected through visual observation and documentation in the form of screenshots. The analysis was conducted in four stages, namely: segment identification, semiotic analysis, interpretation of mathematical concepts, and analysis of meaning and educational implications triangulated with learning theory. The results of the analysis identified seven segments that represent mathematical concepts, including: numbers, addition, subtraction, multiplication, exponents, division, and circles. These findings were synthesized with Duval's register conversion theory, which shows continuous conversion between registers of representation and is aligned with Bruner's cognitive stages (enactive, iconic, symbolic) as a form of visual scaffolding. This visual representation is also relevant to the Learning Outcomes of the Merdeka Curriculum Phases A to F. Thus, this study contributes to enriching theoretical studies on the use of popular digital media as pedagogical tools in mathematics. As a development, future research is expected to implement the use of this video directly in classroom learning practices to empirically test its effectiveness on student learning outcomes, interest, and mathematical representation abilities.